Inflation-Forecast Targeting for India : An Outline of the Analytical Framework - Benes, Jaromir; Clinton, Kevin; George, Asish; John, Joice (Washington, D.C. : International Monetary Fund, 2017)
India formally adopted flexible inflation targeting (FIT) in June 2016 to place price stability, defined in terms of a target CPI inflation, as the primary objective of monetary policy. In this context, the paper draws on Indian macroeconomic developments since 2000 and the experience of other countries that adopted FIT to bring out insights on how credible policy with an emphasis on a strong nominal anchor can reduce the impact of supply shocks and improve macroeconomic stability. For illustrating the key issues given the unique structural characteristics of India and the policy options under an FIT framework, the paper describes an analytical framework using the core quarterly projection model (QPM). Simulations of the QPM are carried out to illustrate the monetary policy responses under different types of uncertainty and to bring out the importance of gaining credibility for improving monetary policy efficacy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet